Population Genetic Structure of Cnesterodon decemmaculatus (Poeciliidae): A Freshwater Look at the Pampa Biome in Southern South America - Ramos-Fregonezi, Aline M. C.; Malabarba, Luiz R.; Fagundes, Nelson J. R. (Frontiers in Genetics, 2017)
The Pampas is a Neotropical biome formed primarily by low altitude grasslands and encompasses the southernmost portion of Brazil, Uruguay and part of Argentina. Despite the high level of endemism, and its significant environmental heterogeneity, Pampean species are underrepresented in phylogeographic studies, especially aquatic organisms. The Pampean hydrological system resulted from a long history of tectonism, climate and sea level changes since the Neogene. In this study, we examined the population genetic structure of Cnesterodon decemmaculatus, a freshwater fish species that occurs throughout most of the Pampa biome. We characterized mitochondrial and autosomal genetic lineages in populations sampled from Southern Brazil and Uruguay to investigate 1) the correspondence between current drainage systems and evolutionary lineages, 2) the demographic history for each genetic lineage, and 3) the temporal depth of these lineages. Overall, we found that the major evolutionary lineages in this species are strongly related to the main Pampean drainage systems, even though stream capture events may have affected the distribution of genetic lineages among drainages. There was evidence for recent population growth in the lineages occupying drainages closest to the shore, which may indicate the effect of quaternary sea-level changes. In general, divergence time estimates among evolutionary lineages were shallow, ranging from 20 to 800 thousand years before present, indicating a geologically recent history for this group, as previously reported in other Pampean species. A Bayesian phylogeographical reconstruction suggested that an ancestral lineage probably colonized the Uruguay river basin, and then expanded throughout the Pampas. This evolutionary scenario may represent useful starting models for other freshwater species having a similar distribution.